TRANSITION FROM ACTIVE TO PASSIVE WEIGHTNING IN NONLINEAR ELASTO-PLASTIC PROCESS - O. L. Shwed; A. A. Abramow (Informatika)
A model of nonlinear elasto-plastic material is proposed. Continuity condition is formulated in transition from an active to passive weighting, which is provided in a regular point of the flow surface with a non-positive specific power of deformation. If the latter condition is not satisfied, there is no transition continuity. In this case, possibility of description of the phenomenon of «locking» the range of high pressure is considered in transition of material from plastic to elastic state.